Planning for practices. Everyday issues in planning considerations using urban green as an example - Jana Kühl (Raumforschung und Raumordnung, 2019)
Discourses in planning theory and in society question the role of planning as decision makers for urban development. Protests of citizens show that their concerns often find too little attention in questions of developing cities. In consequence, a need for rethinking the practice of urban planning becomes apparent. Therefore, it is required to implement an understanding of planning as an integrative process, which is informed by the needs of the people living in the city. At the same time, methods and concepts are needed to identify the heterogeneous concerns of the citizens and to bring them into the planning process. In the first part, the paper presents an idea of citizen-oriented planning practice. In the second part, a methodological framework shows how the differentiated needs of people can be identified and abstracted as a framework which serves as an orientation for decision-making in planning processes. Therefore, the paper refers to approaches of practice theory and focusses on everyday productions of space as a heuristic tool for identifying the needs of people practicing their everyday life. For making it more concrete, the concept is adapted to questions of planning the urban green. Empirical findings show how urban green typically gets relevant in people's practices of everyday life and how planning practice can refer to these findings seeking for a citizen driven urban development.